PENERAPAN KEWENANGAN BAWASLU DALAM PENANGANAN PELANGGARAN PILKADA DI WILAYAH PROVINSI BALI - Agus Surya Manika; Aryadinata, I Putu Yova (Fakultas Hukum Universitas Dwijendra, 2026)
Indonesia is a country of law that implements a democratic system. One form of democracy in Indonesia is the Election with the establishment of the Election Supervisory Body (Bawaslu) which has the authority to examine, review, and handle election violations. In the application of its authority, there is a lack of uniformity in the application of authority between the Gianyar Regency Bawaslu and the Bangli Regency Bawaslu in the 2024 Pilkada. Therefore, this study aims to determine the application of Bawaslu's authority in handling violations of the 2024 Pilkada in the Bali Province and the resolution of Pilkada violations committed by Bawaslu in the Bali Province in 2024. The research method used in this study is an empirical research method, namely field research that aims to intensively study the background of the current situation and social interactions of a social unit, individual, group, institution or community. The conclusion obtained in this study is that the application of Bawaslu's authority in handling Pilkada violations in the Province of Bali in 2024 in its implementation found that there was a lack of uniformity in the application of authority between Bawaslu Gianyar Regency and Bawaslu Bangli Regency where there was a violation of one person voting more than once and the resolution of the violations committed by Bawaslu Gianyar Regency was by means of a Re-vote while Bawaslu Bangli Regency did not conduct a Re-vote. The resolution of election violations is carried out by Bawaslu in the following ways: the stage of receiving reports/findings, the study stage, the results of the study, plenary meetings, follow-ups and recommendations if there is evidence of election violations consisting of violations of the election code of ethics, administrative election violations, and election crimes.